Identification of Dimensions and Components for Implementing E-Learning with an Omnichannel Approach in Upper Secondary Schools - Haghiri Limodehi, Roya; Abdollahi, Mahbubeh; Habibi, Sharare (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study is to identify the critical dimensions and components necessary for implementing e-learning with an omnichannel approach in upper secondary schools. Methodology: This study employed a qualitative research design, involving in-depth interviews with 16 experts in the field of secondary education and e-learning. Participants were selected based on their experience and expertise in educational technology, with criteria including a minimum of five years of relevant work experience and familiarity with the omnichannel approach in education. Data were collected through semi-structured interviews and analyzed using content analysis to identify key themes and components of e-learning implementation. The study ensured the validity and reliability of the findings through expert reviews and the use of Cohen's Kappa coefficient for coding consistency. Findings: The analysis revealed several critical dimensions categorized under "Effective Factors" and "Infrastructure." Key themes identified include the importance of technological infrastructure, security and privacy measures, access management, content customization, communication and collaboration tools, user experience design, continuous management, and financial planning. Additionally, the study highlighted the necessity of a robust Learning Management System (LMS) and the role of secure IT infrastructure in supporting e-learning. These findings align with existing literature and underscore the multifaceted nature of successful e-learning implementation. Conclusion: The study concludes that the successful implementation of e-learning in secondary education requires a comprehensive approach that integrates robust technological infrastructure, security measures, effective content management, and continuous system updates.